The Influence of Multilingualism on the Works of Vasily Sesemann - Julia V. Sokolova (RUDN Journal of Philosophy)
The study is devoted to identifying and analyzing the influence of multilingualism of Vasily Sesemann (1884-1963) on his work. The prerequisites for the formation of natural and acquired multilingualism of V.E. Sesemann are considered. The question is raised about the peculiarities of creativity and language of the philosopher’s works, possible professional advantages due to multilingualism. The research provides an overview of the controversy regarding the national, cultural and philosophical identity of V. Sesemann in the context of professional multilingualism (active academic use of Russian, German and Lithuanian languages). The paper examines the characteristic features of bilinguals and multilinguals, presents a brief overview of the historical dynamics of assessing their cognitive capabilities and the specifics of learning. It is shown that the modern umbrella term metalinguistic awareness helps to identify and describe the specific features inherent in the works of V. Sesemann, his “special grasping of language”, recognizable style, precision of wording and attention to the accuracy of terminology, expressiveness and figurativeness of language, compositional perfection of works. The study reveals that there are a number of additional factors that enhance V. Sesemann’s special attitude to language, including: musical auditory and performing experience, teaching, and work as a translator. In addition, the study demonstrates V. Sesemann’s clear awareness of the opportunities provided by knowledge of several languages, which is supported by the philosopher’s statements and fragments from his children’s memoirs. The work provides examples illustrating the specificity of his style of presentation. The analysis not only shows the uniqueness of V. Sesemann’s phenomenon in the history of philosophy, but also opens up opportunities for new research approaches to his work and demonstrates the research potential of his legacy